Constraints in implementing qlassic for stratified housing / Sofia Nadhirah Harun and Nadira Ahzahar - Harun, Sofia Nadhirah; Ahzahar, Nadira (2018)
QLASSIC was developed by CIDB on 2006 however there is only a small number of projects which applied this assessment. 6% projects were assessed using QLASSIC in 2015 yet it still far from the target 2020. Thus, the objective of this paper was to identify the constraints in implementing QLASSIC for stratified housing. 10 questionnaires were analysed and the highest constraints come from manpower. From the analysis, 90% agreed that the external assessors might come to competitors' company. Other constraints are lack of awareness and confidence in QLASSIQ and CONQUAS is more widely recognized and accepted by construction player. The output of this paper is expected to be beneficial to the contractor and developer in order to set a benchmark on the quality of workmanship for their project so that it can improve their credibility and trust in the eyes of public.